Financing the Underfinanced: Online Lending in China - Wang, Jiazhuo G (Springer, 2015)
This book, as a comprehensive, in-depth analysis of one of the fastest-growing industries in China, covers all the most important areas and issues in the country’s online lending industry. It includes, but is not limited to, the history of online lending, the scale of the online lending market, the basic business models in and a risk analysis of online lending, the characteristics of typical online-lending borrowers and investors/lenders, the root causes of bankruptcy among failed online lending platforms, a comparative analysis of online lending platforms inside and outside China, the overall ranking of online lending platforms in China and finally, the outlook for the online lending industry in the future. The integration of Internet and finance has, in recent years, been among the most notable topics discussed in the media, the business community and academia, both in China and worldwide. The chapters are supplemented with detailed case studies, which include illustrations and tables and the book combines theoretical analysis with conceptual discussions of and best practices in the online lending industry. It will be of interest to a variety of readers worldwide, including: (1) existing and potential online borrowers; (2) existing and potential online lenders; (3) investors and professionals running online lending platforms; (4) traditional bankers and major shareholders in traditional financial institutions; (5) staff in regulatory government agencies; (6) academics; and (7) the general public.